THE IMPACT OF THE COVID-19 PANDEMIC ON THE STOCK PRICES OF MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE (International Journal of Innovative Technologies in Economy, 2024)
The coronavirus, or COVID-19, is caused by the SARS-CoV-2 virus, first discovered in China in late 2019 and as of June 2021. Since then, the virus has spread worldwide. Indonesia has reported more than 31,000 cases of COVID-19 (Gugus Tugas Percepatan Penanganan COVID-19, 2020), making it the second-highest country in ASEAN, according to CNN Indonesia (2022). The global tally has surpassed 6.7 million cases, with over 395,000 fatalities. This pandemic has not only affected the health sector but has also impacted various other economic sectors, including the stock market. Developing countries like Indonesia have felt the repercussions, evident in the movements of the Composite Stock Price Index (IHSG). Studying the IHSG's trends before and during the COVID-19 pandemic is crucial as a guide for governments and companies in managing foreign fund flows, maintaining index stability, and preserving economic value (Nurmasari, 2020). In this context, the Indonesia Stock Exchange (PT. Bursa Efek Indonesia) and the Financial Services Authority (Otoritas Jasa Keuangan or OJK) have introduced new policies to prevent a decline in the capital market caused by Covid-19. The decision by the Indonesia Stock Exchange states that these measures are taken to reduce the spread of the virus.